A CONTRASTIVE ANALYSIS BETWEEN ENGLISH AND INDONESIAN PREPOSITIONS - Yatiningrum, Agung (PEDAGOGY, 2014)
This research studies about English and Indonesian prepositions. The aims of the research are to find the similarities and differences between English and Indonesian prepositions. The data are analyzed using contrastive analysis. In analyzing the data contrastive analysis is employed to find the similarities between English and Indonesian prepositions and to find the differences between English and Indonesian prepositions. The result of the study shows that there are four similarities between English and Indonesian prepositions: (1) Based on the meaning, to indicate the name of city, country, province and place the English prepositional meaning place on, in, and at are similar with Indonesian prepositional meaning place di. (2) Based on the meaning, the English prepositional meaning place above and over are similar with Indonesian prepositional meaning place di atas to indicate the place that higher than a point. (3) Based on The Meaning, the English prepositional meaning place under, underneath, beneath and below are similar with Indonesian prepositional meaning place di bawah to indicate the place that lower than a point. (4) Based on the meaning, the English prepositional meaning place between and among are similar with Indonesian prepositional meaning place di antara to indicate the place on side of a person or thing that has two sides. There are four differences between English and Indonesian prepositional meaning place. (1) Based on the meaning, to indicate the place, Indonesian prepositional meaning place use di while English prepositional meaning place use in, on, and at. (2) Based on the meaning, the use of English prepositional meaning place above and over are different from Indonesian prepositional meaning place di atas to indicate the place that higher than a point. (3) Based on the meaning, the use of English prepositional meaning place under,underneath, beneath and below are different from the Indonesian prepositional meaning place di bawah to indicate the place that lower than a point. (4) Based on the meaning, the use of English prepositional meaning place between and among are different from Indonesian prepositional meaning place di antara to indicate the place on side of a person or thing that has two sides.